If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2j + -4 = 4 Reorder the terms: 6 + -4 + 2j = 4 Combine like terms: 6 + -4 = 2 2 + 2j = 4 Solving 2 + 2j = 4 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2j = 4 + -2 Combine like terms: 2 + -2 = 0 0 + 2j = 4 + -2 2j = 4 + -2 Combine like terms: 4 + -2 = 2 2j = 2 Divide each side by '2'. j = 1 Simplifying j = 1
| -n-(3+9n)=-10-14n | | t+.02t=612 | | 4a+0.2=50 | | 2.9y-4.6=0.6y | | 7z-6z=18+4 | | 2x-3(4x+5)-10=10x+3-4 | | (x-3)(x+3)=2x^2+3x+29 | | 23/6x5/6+23/6x13/6 | | -1/3+2t=-1/3(9t-2) | | D=tres | | y^2-100=4y | | 10y-4y-8=20 | | (u-4)^2/3 | | 4k=60+6k | | 9/5(k-273.15) | | 3-2/6b=1/3b-7 | | k+10/k=4/6 | | 10(x^2-21x+75)=0 | | 5x+2(5x-2)=176 | | 3(2x-2)=4(x+4) | | 8x+10-2x+36=4x+15+8x-28 | | n+1=13-2n+n | | 10y-4-8=20 | | 3(3.99)+1b-0.11=5b | | (2x-3)(2x+3)=55 | | x^2-21x+75=0 | | 5y-4=8+y | | 3x-2=7x+6 | | -4+4/5x=6 | | -5=9+c-4 | | 5x-3+4x-24=3x+2+4x-9 | | -2(6+4b)=-6b |